SISTEM INFORMASI PANGGIL KULI PROYEK (SIPAKUPROY) BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK CODEIGNITER - Bismi, Waeisul; Febriyani, Anisa; Ramadhan, Farid (Universitas PGRI Semarang, 2023)
The development of Website-based information systems has provided significant benefits in terms of distance, time, and accessibility, particularly in the construction industry for finding skilled and experienced construction workers. However, challenges arise in finding qualified workforce due to the phenomenon of globalization. To overcome this issue, SIPAKUPROY is designed as an information system that supports these needs. Through SIPAKUPROY, users can access multiple construction worker teams, obtain detailed pricing information, and follow an efficient payment process. The transition process from manual to digital sales systems, known as digitalization, is a crucial key in implementing SIPAKUPROY, which requires suitable and reliable software and hardware. In the design of SIPAKUPROY, user-friendly design is the main focus, aiming to provide an easy and comfortable user experience. Overall, SIPAKUPROY offers a solution for individuals seeking reliable construction workers without personal connections in the industry. Thus, SIPAKUPROY makes a positive contribution in addressing the challenges faced in finding trustworthy construction workers in this era of globalization.